Current and future treatment options in non-alcoholic steatohepatitis (NASH). (3rd April 2017) - Lazaridis, Nikos; Tsochatzis, Emmanuel
ABSTRACT: Introduction : Non-alcoholic steatohepatitis (NASH) is a chronic liver disease that can progress to cirrhosis and hepatocellular carcinoma. Diagnosis of NASH requires a liver biopsy and is defined as presence of hepatic steatosis, ballooning and lobular inflammation with or without fibrosis. Although NASH is the most common cause of liver disease in the west world and among the top three indications for liver transplantation, there are no universally accepted pharmacological therapies and therapeutic advances have been slow. Areas covered : Current evidence about lifestyle interventions, bariatric surgery and pharmacotherapy is reviewed. Dietary recommendations and lifestyle interventions have shown promising results but are difficult to maintain. At the moment, there is no universally approved medical treatment for NASH. Pioglitazone and vitamin E are recommended by guidelines in selected patients. An increasing number of phase II and III trials in non-cirrhotic NASH are currently recruiting and their preliminary results discussed. Expert commentary : As NASH is classified as a medical condition of an unmet therapeutic need, it has gained an accelerated access pathway for drug approval based on surrogate endpoints. It is therefore expected that within the next five years, there will be at least one approved agent for the pharmacological treatment of pre-cirrhotic NASH.